Direct generation of finite element mesh using 3D laser point cloud. (January 2023) - Cui, Lizhuang; Zhou, Lizhi; Xie, Quanyi; Liu, Jian; Han, Bo; Zhang, Tiantao; Luo, Hongzheng
Abstract: An approach for the finite element (FE) mesh generation of tunnel structures considering the lack of detail, low automation, and intermediate link transformation in the FE mesh generation of tunnels based on the 3D laser point cloud is presented in this paper. To this end, we acquired the tunnel point cloud model using terrestrial laser scanning or mobile laser scanning, and uniform nodes from the raw point cloud using a clock simulation extraction algorithm we developed. In addition, we assign topology information to these nodes. Further, we generated an FE model of the tunnel structure suitable for numerical simulation analysis using Abaqus. We applied the developed method to three types of tunnels; the mesh satisfied the evaluation standards of practical engineering applications. We examined the impact of mesh size and used an engineering example to confirm the method's accuracy. Finally, we provide recommendations for future research considering the future trend of FE mesh generation based on the 3D laser point cloud and its improvements.